Comparison of porous and nano zinc oxide for replacing high-dose dietary regular zinc oxide in weaning piglets. - Lina Long; Jiashun Chen; Yonggang Zhang; Xiao Liang; Hengjia Ni; Bin Zhang; Yulong Yin (PLoS ONE)
The aim of this study was to compare the effect of dietary supplementation with low dose of porous and nano zinc oxide (ZnO) on weaning piglets, and to evaluate the possibility of using them as an alternative to high dose of regular ZnO. Piglets were randomly allocated into four treatment groups fed with four diets: (1) basal diet (NC), (2) NC+ 3000 mg/kg ZnO (PC), (3) NC + 500 mg/kg porous ZnO (HiZ) and (4) NC + 500 mg/kg nano ZnO (ZNP). The result showed that piglets in HiZ group had less diarrhea than ZNP group (P < 0.05). Besides, there was no significant difference between PC, HiZ and ZNP groups in terms of serum malondialdeyhde (MDA) concentration and glutathione peroxidase (GSH-Px) activity (P > 0.05). Analysis of trace metal elements revealed that piglets fed with high dose of regular ZnO had the highest Zn level in kidney (P < 0.05), which may induce kidney stone formation. Additionally, a decrease in ileal crypt depth was observed in PC, HiZ and ZNP group, suggesting an effective protection against intestinal injury. Results of mRNA analysis in intestine showed that ZNP supplementation had better effects on up-regulated trefoil factor 3 (TFF3) and nuclear factor erythroid 2-related factor 2 (Nrf2) levels in duodenum and jejunum than HiZ did (P < 0.05), implying that nano ZnO may possess higher anti-inflammatory capacity than porous ZnO. In conclusion, dietary supplementation with low dose of porous and nano ZnO had similar (even better) effect on improving growth performance and intestinal morphology, reducing diarrhea and intestinal inflammatory as high dose of regular ZnO in weaning piglets. Compared with nano ZnO, porous ZnO had better performance on reducing diarrhea but less effect on up-regulation of intestinal TFF3 and Nrf2.